The politics of interweaving performance cultures : beyond postcolonialism - Amine, Khalid (Routledge advances in theatre and performance studies ;, 2014)
This book provides a timely intervention in the fields of performance studies and theatre history, and to larger issues of global cultural exchange. The authors offer a provocative argument for rethinking the scholarly assessment of how diverse performative cultures interact, how they are interwoven, and how they are dependent upon each other.